2017
DOI: 10.18483/ijsci.1214
|View full text |Cite
|
Sign up to set email alerts
|

Household Dependency on Buffer Zone Community Forest and its Implication for Management of Chitwan National Park, Nepal

Abstract: Conservation of biodiversity in Protected Areas will be more challenging if local communities are heavily dependent on them for various forest products and subsistence needs. Thus this study sought to identify the demographic and socioeconomic variable that influence forest dependency exploring the relationship of forest dependency and household characteristics of the households of the Panbari Buffer Zone Community Forest User Group of Chitwan National Park, Nepal. A sample of 130 households was randomly selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Education level of rural communities can influence households' dependence on forest products use (Timko et al, 2010;Bhandari and Jianhua, 2017). Analysis of educational levels in the two study sites revealed that a significant proportion of household members ended at primary and junior secondary school levels only.…”
Section: Education Levelmentioning
confidence: 97%
See 1 more Smart Citation
“…Education level of rural communities can influence households' dependence on forest products use (Timko et al, 2010;Bhandari and Jianhua, 2017). Analysis of educational levels in the two study sites revealed that a significant proportion of household members ended at primary and junior secondary school levels only.…”
Section: Education Levelmentioning
confidence: 97%
“…This is reinforced by existing research findings in Ethiopia (Mamo et al, 2007), Burkina Faso (Coulibaly-Lingani et al, 2009) and Uganda (Tugume et al, 2015) who observed a positive correlation between dependence on forest products and household size. This suggests that households with large families, especially those with limited income opportunities, are more dependent on forest resources to fulfil their basic needs (see Bhandari and Jianhua, 2017). A study by Ashraf et al (2017) Although large family size constitute a social burden in terms of basic livelihood needs, households with many members of productive and economically active age, use their available labour inputs to an advantage in farming and forest products exploitation.…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…PAs in Nepal functioned initially based on a top-down approach, wherein people-oriented approaches to conservation were ignored (Sharma 2012). To gain the support of local communities in the management of PAs, the Government of Nepal enacted the fourth amendment to the National Parks and Wildlife Conservation Act in 1993 (CNP 2013;Kanel 2012), and promulgated the concept of the buffer zone (BZ) 1 (Bhandari and Zhou, 2017). This was a significant policy transformation and tenure reform for PAs to institutionalize participatory conservation (Thing and Poudel 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, understanding local communities perception is a crucial step toward preparing an appropriate management strategy (Allendorf 2007;Xu et al 2006). Many studies on the CNP have utilized household surveys to assess issues, such as the supply and demand of forest products, contribution of buffer zone management to livelihood support, dependence on forest resources, and household characteristics, to gain a better understanding of the park-people relationship (Bhandari and Zhou 2017;Dhakal and Thapa 2015;Pokharel et al 2018). However, local communities perceptions of the existing forest policy on the use of forest resources in the BZCF have not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Fuelwood derived from both BZCFs and nearby community forests is the main source of energy for many local communities (Thapa 2015). BZCFs support the rural livelihoods, particularly the poor and landless (e.g., Gaire 2006;Paudel 2014;Bhandari and Jianhua 2017) with notable economic values of the products harvested (e.g., Straede and Treue 2006). In fact, poor households were found to have stake and are more supportive of forest conservation (e.g., Stapp et al 2016).…”
Section: Discussionmentioning
confidence: 99%